+0  
 
+1
44
1
avatar

11.49^5x+2=(1/7)^11-x

 Jan 25, 2019
 #1
avatar+97575 
+2

11.49^5x+2=(1/7)^11-x

 

\(11.49^5x+2=(1/7)^{11}-x\\ 11.49^5x+x=(1/7)^{11}-2\\ x(1+11.49^5)=(1/7)^{11}-2\\ x=\frac{(1/7)^{11}-2}{(1+11.49^5)}\)

 

x approx equal  (1/7^11-2)/(1+11.49^5) = -0.0000099868306047

 Jan 25, 2019

31 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.